A comparative analysis of multi-scalar regional inequality in China. Issue 78 (January 2017) - He, Sanwei; Bayrak, Mucahid Mustafa; Lin, Hui
Highlights: Regional inequality is investigated using a comparative and multiscalar framework. Regional inequality is sensitive to geographic scales and regional heterogeneity. The year of 2004 is the turning point of inequality trends in county-level China. Regional policies should adopt a geographic focus to reduce inequalities. Abstract: This paper investigates regional inequality across regions, provinces, prefectures, and counties in China from 1997 to 2010 using a comparative and multiscalar framework. Regional inequality is sensitive to geographic scales and regional heterogeneity. The year 2004 was a turning point for trends in inequality, when a new spatial regime started to emerge at the county-level in China. County-level inequality demonstrates a consistent upward trend despite a slight dip in 2005, which is different from a broad inverted U-shape trend at other geographic scales. Furthermore, intensifying inequalities are demonstrated between prefectures than within prefectures, within provinces than between provinces, and between regions than within regions. The underdeveloped Western region of China contributes the most to regional inequalities across counties and prefectures. Based on the heterogeneous characteristics of regional inequality, it is suggested that effective regional policies should adopt a geographic focus to reduce inequalities. Finally, a Markov chain technique is applied to predict the long-run properties of regional development in China. The results show that it is difficult for counties, prefectures and provinces to leapfrog from being less developed to well developed. This paper concludes that regional inequality in China in the long-run does not follow the neoclassical convergence hypothesis.